Laws and regulations in global financial markets - Girasa, Rosario J. (Palgrave Macmillan, 2013)
The major financial scandals of the past decade, which have been discussed exhaustively in corporate offices by corporate attorneys, and in accounting firms, have led to the passage of massive Congressional enactments in the United States that impact the world of finance. The enactment of the Sarbanes-Oxley Act in 2002, with its significant provisions of 20-year imprisonment for certain offenses, and the conviction of Enron's CEO and other senior executives, finally caught the attention of corporate executives. Laws and Regulations in Global Financial Markets presents students, researchers, and practitioners with an in-depth global analysis of the legal and regulative aspects of corporate financial markets. Readers are introduced to international developments concerning rules and regulations impacting investment advisers and broker-dealers, bankruptcy law, important legal changes influencing banks and credit ratings organizations, real estate regulations, and insurance law. The book concludes with a discussion of personal finance, financial literacy, and federal statutes centered around the subject matter.